Bioceramic sealers in endodontics: integrative review (Research, Society and Development, 2020)
Introduction: Endodontic sealers play an important role in therapeutic success. The properties of bioceramics represent great advances, aiming to meet the needs of other materials available in the market. Objective: To conduct a literature review on the properties and characteristics of bioceramic sealers. Methodology: An integrative literature review was performed, through a search of the Medline database (Medical Literature Analysis and Retrievel System Online). The descriptors used for search were "bioceramic", "endodontic sealer" and "endodontic treatment". The inclusion criteria were articles published in the last ten years, from 2010 to 2020, laboratory and clinical studies, in english and published in full. Duplicate articles, literature reviews, studies with only the available abstract, dissertations, monographs and theses were excluded. Results: After the search of the articles, 50 articles on bioceramic sealers were included in the literature review. The articles had as objectives of study the chemical, physical and biological properties, in addition to marginal adaptation, apical sealing and the behavior of materials in relation to retreatment. Conclusion: It can be concluded that the use of bioceramic sealers presents favorable and promising aspects, although more clinical studies need to be conducted.Parte inferior do formulário.